Legitimasi Pencabutan Kewarganegaraan dalam Hukum Hak Asasi Manusia Internasional: Studi Kasus di Nikaragua - Calvin Paulus Marcelito Simanjuntak; Diajeng Wulan Christianti (Jurnal HAM, 2025)
The right to nationality is a fundamental prerequisite for accessing other human rights, yet its arbitrary deprivation remains a critical concern under international law. This study examines Nicaragua's Laws No. 1055 and 1145, which authorize the revocation of citizenship based on an expanded and ambiguous definition of "treason," encompassing peaceful political acts such as supporting international sanctions. This case demonstrates how nationality, often described as the "right to have rights," is weaponized for political purposes, revealing how the misuse of citizenship laws threatens the integrity of international human rights protections against statelessness. Specifically, the study investigates whether this definition justifies nationality deprivation under the standards of the 1961 Statelessness Convention and whether such measures violate the right to freedom of expression, as protected by Article 19 of the ICCPR. Utilizing a normative juridical approach, the research analyzes international legal instruments alongside Nicaraguan domestic law and incorporates secondary data from organizations such as UNHCR. The findings reveal that Nicaragua's practices fail to satisfy the criteria of legality, necessity, and proportionality under international human rights law and instead constitute a form of political repression. Such measures not only undermine the purpose of the 1961 Statelessness Convention but also exemplify how nationality laws can be distorted to silence dissent. Therefore, this study underscores the urgent need for stronger international safeguards against arbitrary deprivation of nationality.